Photoinduced on-chain charge-separation and ultrafast recombination in a sugar-coated insulated molecular wire - Mroz, M; Lanzani, G; Virgili, T; Mc Donnell, S; Frampton, M; Anderson, H (2009)
Transient absorption three-beam pump-push-probe experiments demonstrate that cyclodextrin-encapsulation of conjugated polymer chains prevents interchain effects, such as energy migration and charge hopping. In the unencapsulated polymer, transient population of high-lying singlet states leads to interchain ionization, generating long-lived charge-separated species. Supramolecular encapsulation prevents this process; with high-lying singlets undergoing on-chain ionization, followed by very rapid charge recombination. Threading is an efficient way to control charge recombination and to obtain a material suitable for photonic applications, where the push effect can be implemented for all-optical ultrafast switching. © 2009 The American Physical Society.